Poetry and the making of the English literary past, 1660-1781 - Terry, Richard (Richard G.) (Oxford Oxford University Press, 2001)
Exploring how the English literary past was made, this book charts how antiquarians have unearthed the raw materials of the British tradition and how critics assigned the leading writers to canons of literary greatness.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: English literature -- History and criticism -- Theory, etc. -- 17th century; English literature -- History and criticism -- Theory, etc. -- 18th century; Canon (Literature)